2005
DOI: 10.5172/conu.19.1-2.32
|View full text |Cite
|
Sign up to set email alerts
|

Understanding mentoring and preceptorship: Clarifying the quagmire

Abstract: Mentoring! Preceptorship! These two terms are widely used within nursing. The vast literature on mentoring and preceptorship defines these concepts as discrete roles. However, confusion exists as to what defines mentorship when compared to preceptorship. It is apparent that these terms are being used interchangeably, despite the obvious and not so obvious differences portrayed in the literature. The authors therefore have questioned whether the roles of a mentor and preceptor are discrete and unique or can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…The nurse dyad relies on the relationship in large measure for a period of several years for professional outcomes, such as research and scholarship; an expanded knowledge and practice base; affirmative action; and/or career progression. Mentoring nurses tend to repeat the process with other nurses for the socialization of [clinicians], scholars and scientists into the professional community and for the proliferation of a body of nursing knowledge (1996: 315). of mentoring (Barker, 2006) and the outcomes of mentoring (Firtko et al, 2005). Only recently has there been a shift in focus to examine the actual experience of either mentors or mentees in relation to the traditional triumvirate of nurse mentoring (Waters et al, 2003;Carroll, 2004;Gibb et al, 2004Gibb et al, , 2006Beecroft et al, 2006;Stewart, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…The nurse dyad relies on the relationship in large measure for a period of several years for professional outcomes, such as research and scholarship; an expanded knowledge and practice base; affirmative action; and/or career progression. Mentoring nurses tend to repeat the process with other nurses for the socialization of [clinicians], scholars and scientists into the professional community and for the proliferation of a body of nursing knowledge (1996: 315). of mentoring (Barker, 2006) and the outcomes of mentoring (Firtko et al, 2005). Only recently has there been a shift in focus to examine the actual experience of either mentors or mentees in relation to the traditional triumvirate of nurse mentoring (Waters et al, 2003;Carroll, 2004;Gibb et al, 2004Gibb et al, , 2006Beecroft et al, 2006;Stewart, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…This may have limited learning opportunities focused on clinical competency development (Henzi et al 2006). There is potential value in reviewing the concept of preceptorship in supporting the newly graduated physiotherapist's orientation to the workplace but also -possibly more significantly -for the development of clinical and professional expertise (Firtfo et al 2005). In a review of medical doctor training, Kennedy et al (2005) found that there is a lack of empirical research as to how and when progressively to give learners independence.…”
Section: Discussionmentioning
confidence: 99%
“…This has arisen because of the overlap of mentoring with the concepts of preceptorship and clinical supervision (Firtko et al, 2005).…”
Section: Dimensions Of Mentoringmentioning
confidence: 99%